SI PARASIT LAJANG: POTRET PEREMPUAN METROPOLITAN - Saksono Prijanto (Madah: Jurnal Bahasa dan Sastra, 2014)
The presence of novel Saman by Ayu Utami surprised the world of Indonesian literature. Response to readers and literary critics of Saman diverse, both those in favor, cursing and not be silent. Ayu Utami is a productive female novelist because she continuously  has been published novel Saman and Larung (dualogy), Serial Numbers Fu (Manjali and Cakrabirawa and Lalita), and the trilogy (Parasit Lajang, Enrico Love Story, Parasit Lajang—Ex Parasit Lajang). Ayu Utami‟s achievement in writing, among others  are "Mastera Young Writers Award 2009" in 2009. The purpose of  this article is to express the position and idea of young metropolitan woman, their  restless  in seeing the domestic life. I figure (women) in the novel The Parasit Lajang (SPL) minds that  women should have equality to men legally in many ways, especially on marriage. SPL novel deserves to be read and studied intensively, both as evidence of freedom in the creative process of a writer (female) as well as the Indonesian literary enrichment effort for the reader of literature, literary observers, as well as researchers in Indonesian literature. Kehadiran Ayu Utami melalui novel Saman mengagetkan dunia sastra Indonesia. Tanggapan pembaca serta kritikus sastra terhadap Saman beragam, baik mereka yang memihak, memaki, maupun yang diam tidak bersikap. Novelis perempuan ini termasuk produktif karena berturut-turut telah menerbitkan novel Saman dan Larung (dwilogi), Seri Bilangan Fu (Manjali dan Cakrabirawa serta Lalita), dan trilogi (Si Parasit Lajang, Cerita Cinta Enrico, dan Pengakuan Eks Si Parasit Lajang). Prestasi Ayu Utami dalam tulismenulis, antara lain memperoleh ―Penghargaan Sastrawan Muda Mastera 2009‖ pada tahun 2009. Tujuan penulisan artikel ini adalah mengungkapkan sikap dan pandangan hidup perempuan muda metropolitan tersebut, sekaligus kegelisahannya dalam menyikapi suatu kehidupan rumah tangga. Tokoh saya (perempuan) dalam novel Si Parasit Lajang (SPL) berpegang teguh pada sikapnya, yaitu perempuan harus memiliki kesetaraan terhadap laki-laki secara hukum dalam berbagai hal, khususnya tentang perkawinan. Novel SPL layak dibaca dan diteliti secara intensif, baik sebagai bukti kebebasan dalam proses kreatif dari seorang pengarang (perempuan) Indonesia maupun sebagai upaya pengayaan literer bagi pembaca sastra, pengamat sastra, serta peneliti sastra di Indonesia.